2023
DOI: 10.1007/s11356-023-27891-5
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten oxide nanostructures peculiarity and photocatalytic activity for the efficient elimination of the organic pollutant

Abstract: For the rst time, the effect of gemini based twin-tail and conventional surfactant on tungsten oxide nanostructures and their e cacy for the elimination of the organic pollutant is studied. The tungsten oxide nanostructures were synthesized by a simple hydrothermal route in the presence of C 14 TAB and gemini based twin-tail surfactant. The impact of using these special shape and size directing agents for the synthesis of nanostructures was observed in the form of different shapes and sizes. The tungsten oxide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Further, Jamwal et al used the hydrothermal method to synthesize tungsten trioxide (WO 3 ) with two different surfactants (CTAB and TTS). The surfactants influenced the WO 3 crystal shape, forming chain-like structures with CTAB and cubes with TTS . Jaiswal et al reported a series of reactions to achieve WO 3 nanoribbon via hydrothermal reactions (24–48 h) at temperatures ranging from 120 °C (pale-yellow product) to 650 °C (greenish-yellow product) with an intermediate phase with pale-white at 350 °C .…”
Section: Introductionmentioning
confidence: 99%
“…Further, Jamwal et al used the hydrothermal method to synthesize tungsten trioxide (WO 3 ) with two different surfactants (CTAB and TTS). The surfactants influenced the WO 3 crystal shape, forming chain-like structures with CTAB and cubes with TTS . Jaiswal et al reported a series of reactions to achieve WO 3 nanoribbon via hydrothermal reactions (24–48 h) at temperatures ranging from 120 °C (pale-yellow product) to 650 °C (greenish-yellow product) with an intermediate phase with pale-white at 350 °C .…”
Section: Introductionmentioning
confidence: 99%